Assessing passengers’ satisfaction level on bus services in selected urban and rural centres of Peninsular Malaysia - Mohamed Osman, Mariana; Ponrahono, Zakiah; Bachok, Syahriah; Ibrahim, Mansor (Elsevier, 2016)
This research highlights the urban-rural bus services passenger's satisfaction level in the selected settlements in Peninsular Malaysia. Johor is to represent the southern states while Penang is to represent the northern states. For eastern-coast states, Pahang is selected while Perak is to represent a still developing state, which is yet to reach the advanced level of large conurbations. The main objectives are to evaluate the bus service quality through passengers’ satisfaction survey. A total of 1130 survey questionnaire forms are collected. The result shows socio-demographic and trip characteristics influenced the satisfaction level and passengers’ expectation of future bus services improvements.